Product Quality Price and Image Brands Against Purchase Decisions - Budi Rahayu; Rumanintya Lisaria Putri; Joko Sutrisno (Journal of Industrial Engineering and Management, 2023)
Changes in an increasingly fast world require companies to respond to changes that occur; the main problem facing companies today is how the company attracts customers to see and buy so that the company continues to grow. This goal will be achieved if a company wants to do marketing by participating in the UMKM bazaar or competitions so that the products offered are solidly known and can attract a consumer's purchase request. To get consumers willing to make purchases, entrepreneurs must develop strategic plans, including improving product quality, paying attention to product prices, and providing a good brand image. Hence, consumers feel confident about their products. Product to be purchased. This study analyzes product quality, price, and brand image buying batik at the Numansa Batik Kediri boutique. The technique used is probability sampling, and the number of samples obtained is 40 respondents. The data analysis tool used SPSS Version 22. The analysis results showed a positive and significant influence between product quality and batik purchasing decisions at the Numansa Batik boutique, where t counted 3,787 with a substantial value of t 0.001 0.05, which means that there is a significant influence on brand image. On purchasing decisions, there is a positive and significant influence between product quality, price, and brand image on buying decisions at the Numansa Batik boutique, where F counts 11,661 with a substantial value of F 0.00 0.05. Based on the research results, Numansa Batik Boutique seeks to increase prices, provide appropriate service quality, and improve the quality of Numansa Batik Boutique products.